Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-96893-5
|View full text |Cite
|
Sign up to set email alerts
|

Alpha activity neuromodulation induced by individual alpha-based neurofeedback learning in ecological context: a double-blind randomized study

Abstract: The neuromodulation induced by neurofeedback training (NFT) remains a matter of debate. Investigating the modulation of brain activity specifically associated with NF requires controlling for multiple factors, such as reward, performance, congruency between task and targeted brain activity. This can be achieved using sham feedback (FB) control condition, equating all aspects of the experiment but the link between brain activity and FB. We aimed at investigating the modulation of individual alpha EEG activity i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 100 publications
(146 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, neuromodulation of alpha activity was shown to be a true effect, as participants had significantly modulated alpha activity post-intervention compared with pre-intervention. This indicates that Axon NFB led to participants modulating their own alpha activity, which has been demonstrated to be a longitudinal effect over many training sessions ( 16 , 34 ). It also supports the use of purposely designed low stimulus NFB games, which allowed the participant to feel relaxed but not overstimulated, indicating the stimulus was appropriate and effective.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, neuromodulation of alpha activity was shown to be a true effect, as participants had significantly modulated alpha activity post-intervention compared with pre-intervention. This indicates that Axon NFB led to participants modulating their own alpha activity, which has been demonstrated to be a longitudinal effect over many training sessions ( 16 , 34 ). It also supports the use of purposely designed low stimulus NFB games, which allowed the participant to feel relaxed but not overstimulated, indicating the stimulus was appropriate and effective.…”
Section: Discussionmentioning
confidence: 72%
“…To assess whether the intervention had a significant effect on the targeted alpha band oscillations, a paired two-tailed Student's t -test comparing pre- (first five training sessions) and post- (last five training sessions) alpha power (pre-training baseline, eyes-opened) was performed. This method provided a larger, more realistic data set, as alpha activity is a spontaneous but complex rhythm associated with several cognitive states and processes ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
“… Fell et al (2010) propose that for beginners, meditation states are related to cognitive processes that are also found in non-meditative exercises, that is alpha and theta. These relate to internalizing attention, relaxation, and cognitive effort, which are easiest to modulate by cognitive control ( Kubota et al, 2001 ; Grosselin et al, 2021 ; McFerren et al, 2021 ). In intermediate practitioners, gamma waves are altered, which could be involved in reaching novel states of consciousness through learning ( Axmacher et al, 2006 ).…”
Section: The Neuroscientific Perspective: a Brief Overview Of Meditat...mentioning
confidence: 99%
“…In contrast, EEG-feedback protocols for mindfulness-related brain activity aim to reinforce activity in alpha and theta bands with positive feedback while decreasing high beta activity [ 45 , 46 , 47 , 48 ]. Additionally, studies of mindfulness training and alpha-based neurofeedback training have found that both can lead to increases in alpha power and mindful awareness, and have proposed alpha as a mediator of the training effect on cognitive functioning [ 45 , 46 , 49 , 50 , 51 , 52 , 53 , 54 ]. This improvement in regulating alpha waves exerts its positive influence on learning by allocating attentional resources more fully during early processing phases and by the neuromodulation of beta waves to slower alpha waves, the process of which is responsible for memory consolidation [ 29 , 55 ].…”
Section: Introductionmentioning
confidence: 99%